2005
DOI: 10.1128/jb.187.11.3708-3712.2005
|View full text |Cite
|
Sign up to set email alerts
|

16S rRNA Mutations That Confer Tetracycline Resistance inHelicobacter pyloriDecrease Drug Binding inEscherichia coliRibosomes

Abstract: Tetracycline resistance in clinical isolates of Helicobacter pylori has been associated with nucleotide substitutions at positions 965 to 967 in the 16S rRNA. We constructed mutants which had different sequences at 965 to 967 in the 16S rRNA gene present on a multicopy plasmid in Escherichia coli strain TA527, in which all seven rrn genes were deleted. The MICs for tetracycline of all mutants having single, double, or triple substitutions at the 965 to 967 region that were previously found in highly resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 26 publications
1
27
1
2
Order By: Relevance
“…To relax the selective pressure on ribosome function in the presence of the U1052G mutation, a randomized plasmid library of positions 965-967 was subsequently constructed. Equivalent libraries have been used to isolate mutants with tetracycline resistance (24). Using this approach, multiple tetracycline-resistant mutants with sequence variations at positions 965-967 were identified.…”
Section: Resultsmentioning
confidence: 99%
“…To relax the selective pressure on ribosome function in the presence of the U1052G mutation, a randomized plasmid library of positions 965-967 was subsequently constructed. Equivalent libraries have been used to isolate mutants with tetracycline resistance (24). Using this approach, multiple tetracycline-resistant mutants with sequence variations at positions 965-967 were identified.…”
Section: Resultsmentioning
confidence: 99%
“…the crucial part of primary acceptor site (site P) is recognized as the major mechanism of tetracy cline resistance. The main point mutation is a substitution of an AGA with a TTC triplet [59,60] and it reduces the affinity of 24%-52% [61] . Levels of resistance are proportional to the number of changes in the AGA 965-967.…”
Section: Tetracyclinementioning
confidence: 99%
“…Purine-rich sequences in the loop of helix 31 are more frequently observed in susceptible strains, whilst pyrimidine-rich loops are in the resistant strains. It is possible that pyrimidine-rich sequences in helix 31 are not compatible with tetracycline conformation, leading to a decreasing affinity [60] . Another study found a deletion of G942 in all resistant strains.…”
Section: Tetracyclinementioning
confidence: 99%
“…These mutations have been shown to occur in the tetracycline highaffinity binding sites on the ribosomal 30S subunit (which are often base-paired regions) and are believed to lead to conformational changes that hamper base pairing and affect drug binding (10,23,58). They have also been shown to decrease drug binding in direct proportion to the number of base mutations (63,64). Hence, all the resistance mechanisms against the tetracyclines appear to involve decreased drug binding in some way and indicate the involvement of these binding sites in the mechanism of action of the tetracyclines.…”
Section: Mechanism(s) Of Action Of the Tetracyclines: The Journey So Farmentioning
confidence: 99%